O valor diagnóstico das avaliações combinadas de dor e funcionalidade para desordem temporomandibular crônica em mulheres brasileiras - Barbosa, Michelle Cristina Sales Almeida (2018)
Temporomandibular joint dysfunction (TMD) with a multifactorial etiology of the temporomandibular joint (TMJ) is the second most frequent cause of orofacial pain in the world. Evidence indicates that TMD pain is related to masticatory muscle hyperactivity. The research diagnostic criteria for temporomandibular disorders (RDC/TMD) considered internationally as the gold standard for diagnosing TMD requires a trained and familiar professional in addition to a significant amount of time for their application. The combination of measures of pain and functionality, through a proven statistical model could provide an efficient response to the diagnosis of TMD. Objective: to investigate the response capacity resulting from the arrangement between variables to discriminate individuals with and without TMD Methodology: A cross-sectional study was carried out in 98 women (29 ± 6 years), with RDC / TMD, assigned to two groups, with and without TMD. The visual analogue scale (VAS) and pressure pain threshold (PPT) of the TMJ (or algometro) were used to evaluate pain, EMG was used to evaluate muscular and temporal excitability, and the mandibular functional limitation index (MIFQ) was used for evaluate function. The data were monitored through a timer, individually verified by the Receiver Operator Characteristics (ROC) curve and combined using a generalized linear model. The data were monitored through a timer, individually verified by the Receiver Operator Characteristics (ROC) curve and combined using a generalized linear model. The Mann-Whitney test defined the differences between groups. Results: Two statistical models were obtained, with and without PPT, and presented higher sensitivity (Se), specificity (Sp) and precision (Se = 0.95 / 0.95, Sp = 0.81 / 0.80, error = 0.10 / 0.11, 0.31 / 0.30, respectively) compared to the individual ROC curve results. The temporal efficiency of RDC / TMD (~ 30 min) was lower than VAS + PPT + MFIQ (~ 5min). Conclusion: The estimated linear model showed a more adequate responsiveness and greater precision to discriminate women with and without TMD than the individual parameters.